Heat Penetration and Quality Characteristics of Ready-To-Eat Thermally Processed Mangalorean-Style Squid Rings in Masala in Retort Pouch - Gundubilli, Devika; Bojayanaik, Manjanaik; Thachil, Madonna Thomson; Dasan, Gouthamy Puthanangadi; Chavan, Sachin Dnyanoba; Tekade, Vyankatesh; Tameshwar; Siravati, Maga Raju; Banavath, Srinu Nayak; Alandur, Veena Shetty; Mohan, Chitradurga Obaiah (Fishery Technology, 2026)
The present work aimed to optimize the thermal processing of Mangalorean-style squid rings in masala in a retort pouch and evaluate its sensory and textural changes during storage. The recipe was developed based on the authentic culinary style prevalent in Mangaluru, Karnataka, India, followed by sensory evaluation. Mangalorean-style squid rings in masala (270 ± 10 g) were packed in retort pouches, steam exhausted, heat sealed, and thermally processed at selected F0 values (10 and 12 min) and stored for 90 days. Thermal processing caused a slight increase in TVBN and TBARS values compared to raw squid but no significant differences were observed between the two F0 treatments. The sensory characteristics and texture profile of the products remained comparable between treatments after 90 days of storage. The cook values at F0 10 and 12 minutes were 81.54 and 94.05 min, respectively, indicating greater thermal impact at higher processing intensity. Thermal processing at F0 10 minutes resulted in a 19.46% reduction in total process time compared to F0 12 minutes, demonstrating improved heating efficiency. Accordingly, an F0 value of 10 min was identified as the optimal processing condition for the preparation of ready-to-eat ‘Mangalorean-style’ squid rings in masala using retort pouch technology.